Social Actor Representation in Prabowo Subianto’s 2024 Debate Discourse - Silaban, Jelly Prima Krisnawati; Ilma, Dzikri; Sembiring, Pemina Br.; Sinar, T. Silvana (Universitas Pamulang, 2025)
This study examines how social actors are represented in Prabowo Subianto’s discourse during the first 2024 Indonesian presidential debate. Drawing on Theo van Leeuwen’s (2008) Social Actor Theory within the framework of Critical Discourse Analysis (CDA), the study analyzes seventeen selected utterances to uncover the ideological and discursive strategies employed to construct political identity and reinforce legitimacy. Using a qualitative descriptive design, the data were obtained from the official debate transcript and analyzed through categorization of inclusion, exclusion, activation, personalization, and other representation strategies. The findings reveal that Prabowo frequently activates himself as a patriotic reformer, elevates the people as sovereign decision-makers, background institutions, and subtly delegitimizes political opponents through irony, contrast, and historical recontextualization. The study also shows how humor, metaphor, and informal language are strategically used to foster emotional proximity with the public. These strategies contribute to building a persuasive and ideologically charged public persona. The results demonstrate that live political performance in presidential debates functions as a site of symbolic authority construction and ideological negotiation. This research offers both theoretical and empirical contributions to discourse studies and political communication, particularly in the context of contemporary Indonesian democracy.